Combination of contrast-enhanced wall motion analysis and myocardial deformation imaging during dobutamine stress echocardiography. (3rd September 2014) - Nagy, Anikó I.; Sahlén, Anders; Manouras, Aristomenis; Henareh, Loghman; da Silva, Cristina; Günyeli, Elif; Apor, Astrid A.; Merkely, Béla; Winter, Reidar
Abstract: Background: The combination of deformation analysis with conventional wall motion scoring (WMS) has been shown to increase the diagnostic sensitivity of dobutamine stress echocardiography (DSE). The feasibility and diagnostic power of WMS is largely improved by contrast agents; however, they are not used in combination with deformation analysis, as contrast agents are generally considered to render strain measurement unfeasible. Aims: To assess the feasibility of tissue velocity (TVI)- and 2D speckle tracking (ST)-based strain analysis during contrast-enhanced DSE; and to show whether there is an incremental value in combining deformation analysis with contrast-enhanced WMS. Methods: DS echocardiograms containing native, tissue Doppler, and contrast-enhanced loops of 60 patients were analysed retrospectively. The feasibility of WMS, TVI-, and ST-strain measurement was determined in 40 patients according to pre-defined criteria. The diagnostic ability of a combined protocol integrating data from contrast-WMS and TVI-strain measurement was then compared with contrast-WMS alone in all 60 patients, using coronary angiograms as a gold standard. Results: Both TVI- and ST-based strain analysis were feasible during contrast-DSE (feasibility at peak stress: 87 and 75%). At the patient level, the diagnostic accuracy of the combined method did not prove superior to contrast-WMS (82 vs. 78%); a trend towards improved sensitivity and specificity for detecting coronary artery disease in the right coronary artery circulation (sensitivity: 85 vs. 77%, P = NS; specificity: 96 vs. 94%) was, however, observed. Conclusion: Both TVI- and ST-based myocardial deformation analysis are feasible during contrast-enhanced DSE, however, our results fail to demonstrate a clear diagnostic benefit of additional strain analysis over expert WMS alone.